PEMANFAATAN DIGITAL HISTORY UNTUK PEMBELAJARAN SEJARAH LOKAL - Indah Wahyu Puji Utami (Universitas Negeri Malang, 2020)
This article aims to provide some reflections regarding instructional praxis in the amidst of global pandemic and insights of digital history as an alternative solution that can be used for local history learning in this unprecedented situation. In doing so, research problems were formulated, data (especially from peer-reviewed articles) were gathered, corroborated, presented and discussed accordingly. This study finds that Covid-19 has changed the educational landscape worldwide, including Indonesia. Given the unfortunate condition of the pandemic, many educational institutions shifted their teaching and learning into online. It provides various challenges as well as opportunities to use various new digital media in education, including digital history. Emerged in the late 20th century, digital history provides opportunities for history teachers or educators to use it as sources of history learning, especially on local history. Using various primary sources available online, teachers could design new instructional materials or project-based learning on local history.